Heuristic Bias and Loss Aversion Impact in Stock Investment Decision Making in Batam - Fendy Cuandra; Michael Setiawan; Candy Candy; Hesniati Hesniati (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2025)
Technological advancements affect an individual's financial management by increasing spending and necessitating investments to meet these needs. This research intends to analyze the effect of heuristic bias and loss aversion on investment decision. This study uses the investment decision variable to be the dependent variable and uses overconfidence, availability, representativeness, anchoring, gambler fallacy, and loss aversion to be the independent variables. This study uses the SmartPLS application to analyze data and uses an online questionnaire to collect respondents' answers. Sampling was conducted using purposive sampling technique to collect samples from investors in Batam. The study shows that gambler fallacy, loss aversion, overconfidence and representativeness bias have a significant positive impact on investment decisions, while anchoring and availability bias have no significant impact on investment decisions.